Influência da aplicação de ultrassom em desidratação osmótica de carne bovina - Carvalho, Gisandro Reis de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Brining is an employed process in meat products that allows reducing the amount of water, making them more stable. The combination of brining with others technologies results in greater process efficiency. Nowadays, due to its wide field of action, ultrasound technology has been applied in food industry, where one of its great advantages is the improved process kinetic. Therefore, the present project aims to study the influence of ultrasound application in the osmotic dehydration process. Initially, meat was chemically characterized. The thermophysical properties (density, dynamic viscosity, specific heat and thermal conductivity) of salt solutions were determined experimentally as a function of concentration and temperature. The kinetic of dehydration was determined by an experimental central composite design involving the variables ultrasonic power and sodium chloride concentration. Empirical and semi-empirical models were employed to the physical and thermal properties of sodium chloride solutions modeling and simulation, as well as the experimental dehydration kinetics, obtaining acceptable statistical fitting results. In addition to the osmotic dehydration assisted with ultrasound modeling was applied the stepwise regression method to construct a model that allows evaluate the moisture content as a function of time, salt concentration and ultrasound power within an experimental data range. Thermo-physical properties were similar to those reported in the literature. The density ranged from 1005,2 to 1178,5 kg∙m-3, while the viscosity showed values from 0.536 to 2.198 mPa∙s, these properties were directly proportional to concentration and inversely to temperature. The specific heat varied from 3.312 to 4.011 kJ∙kg-1∙°C-1, while the thermal conductivity showed values from 0.490 from 0.614 W∙m-1∙°C-1, these two properties were inversely proportional to concentration and only the conductivity showed increase in their values ...

A desidratação osmótica é um processo empregado em produtos cárneos, que permite a redução da quantidade de água, tornando-os mais estáveis. A combinação da desidratação osmótica com outras tecnologias resulta em maior eficiência do processo. Atualmente, devido a seu amplo campo de ação, a tecnologia de ultrassom vem sendo empregada na indústria de alimentos, onde uma de suas grandes vantagens é a melhora na cinética de processos. Assim, o presente trabalho teve como objetivo avaliar a influência da aplicação de ultrassom no processo de desidratação osmótica de carne bovina. Inicialmente, foi feita uma caracterização química do miolo da paleta bovina. Também foram determinadas experimentalmente, em função da concentração e temperatura, as propriedades termofísicas: densidade, viscosidade dinâmica, calor específico e condutividade térmica de soluções de cloreto de sódio. A cinética de desidratação foi realizada conforme estabelecido por um planejamento experimental central composto envolvendo as variáveis: potência ultrassônica e concentração de cloreto de sódio. Modelos empíricos e semi-empirícos foram empregados para a modelagem e simulação das propriedades termo-físicas de soluções de cloreto de sódio, bem como para a cinética de desidratação osmótica. Em complementação à modelagem do processo de desidratação osmótica assistida com ultrassom, foi aplicada a metodologia de regressão passo a passo para a construção de um modelo capaz de predizer o conteúdo de umidade em função do tempo, concentração de cloreto de sódio e potência de ultrassom, dentro da faixa dos valores experimentais. Para as propriedades termo-físicas, foram obtidos valores semelhantes aos reportados na literatura. A densidade variou de 1005,2 a 1178,5 kg∙m-3, já a viscosidade apresentou valores de 0,536 a 2,198 mPa∙s, sendo estas duas propriedades diretamente proporcionais à concentração ...
Keywords: Tecnologia de alimentos; Carne bovina - Conservação; Carne bovina - Desidratação; Alimentos - Desidratação; Modelagem de processos; Ultrassom; Food technology